TORCH seroprevalence in pregnant women from peri-urban Iquitos in the Amazon jungle of Peru - Cabrera Sosa, Luis (2019)
ABSTRACT TORCH infections are acquired during pregnancy and can cause abnormal fetal development. These infections include toxoplasmosis, rubella, cytomegalovirus (CMV), herpes simplex (HSV) and others. As part of clinical care in Peru, there is no routine testing for the TORCH infections listed above. As a part of the ZIP study, 350 pregnant women have been enrolled in their first or early second trimester from peri-urban communities in Iquitos, Peru. Blood samples have been collected at enrollment to test for syphilis, HIV and TORCH. We determined the seroprevalence of toxoplasmosis, CMV, rubella, and HSV in these women using a commercial ELISA for IgM. The mean age of the women enrolled was 26.2 ± 6.6 years, the gestational age at sample collection was 13.2 ± 3.4 weeks, and 31% were primigravida. Three (0.9%) sample was positive for syphilis and 4 (1.1%) for HIV. Twenty one (6%) samples were positive for Toxoplasma gondii, 66 (18.9%) for CMV, 18 (5.1%) for rubella, and 109 (31.1%) for HSV 1 or 2. Almost half of the women (159, 45.4%) had negative IgM for all TORCH infections, and 2 (0.6%) were positive for all. The most frequent profile was an IgM positive only for HSV (53, 15.1%) and only for CMV (22, 6.3%). The high IgM seroprevalence of TORCH infections found in this study provides evidence to support local routine testing during pregnancy by the Ministry of Health. In addition, in order to maintain the elimination of congenital rubella in the region, it is important to strive for high immunization rates with MMR (measles, mumps and rubella)